KIR channels tune electrical communication in cerebral arteries. Issue 6 (June 2017) - Sancho, Maria; Samson, Nina C; Hald, Bjorn O; Hashad, Ahmed M; Marrelli, Sean P; Brett, Suzanne E; Welsh, Donald G
The conducted vasomotor response reflects electrical communication in the arterial wall and the distance signals spread is regulated by three factors including resident ion channels. This study defined the role of inward-rectifying K + channels (KIR ) in governing electrical communication along hamster cerebral arteries. Focal KCl application induced a vasoconstriction that conducted robustly, indicative of electrical communication among cells. Inhibiting dominant K + conductances had no attenuating effect, the exception being Ba 2+ blockade of KIR . Electrophysiology and Q-PCR analysis of smooth muscle cells revealed a Ba 2+ -sensitive KIR current comprised of KIR 2.1/2.2 subunits. This current was surprisingly small and when incorporated into a model, failed to account for the observed changes in conduction. We theorized a second population of KIR channels exist and consistent with this idea, a robust Ba 2+ -sensitive KIR 2.1/2.2 current was observed in endothelial cells. When both KIR currents were incorporated into, and then inhibited in our model, conduction decay was substantive, aligning with experiments. Enhanced decay was ascribed to the rightward shift in membrane potential and the increased feedback arising from voltage-dependent-K + channels. In summary, this study shows that two KIR populations work collaboratively to govern electrical communication and the spread of vasomotor responses along cerebral arteries.